Phototherapy as a therapeutic technique for an alternative treatment in Malaysia case study: Myanmar refugees, Malaysia / Ellyana M.M.Tan ... [et al.] - M.Tan, Ellyana M.; Rahim, Ruslan; M. Jarit, Mastura; Senin, Noorhaslina (2019)
This research employs the benefit of Photo Elicitation Interview (PEI) as part of a therapeutic technique of sharing experience for Myanmar Refugees in Malaysia. This ongoing process might be utilised in different ways from time to time. The research featured a random audience of Myanmar Refugees, aged 7 to 55 years old. Each participant was asked to pick one from 200 random images that reflected their background, ethnicity, visual experience preferences and interest. From one random image, participants were asked to talk about the visual chosen. This study used only ONE (1) Phototherapy technique, which is the Photo Elicitation Interview (PEI). The study aims to see if the PEI Phototherapy can become part of the therapeutic process. The methodology adopted for this study was based on qualitative interviews. In the discussion of the result, this research has developed an appropriate framework. From these observations, the research found that Phototherapy evokes the communication process by indirectly encouraging people to open up and talk while describing the visual. The result from this research aims to provide data for any related agency, art therapy guidelines and a method for determining individual emotional states.